ChemInform Abstract: Single‐Crystalline Octahedral Au—Ag Nanoframes. Issue 13 (18th March 2013) - Hong, Xun; Wang, Dingsheng; Cai, Shuangfei; Rong, Hongpan; Li, Yadong
Abstract Octahedral Au—Ag nanoframes are prepared by reaction of AgNO3 with CuCl in octadecylamine solution at 115 °C, followed by dropwise addition of HAuCl4 solution (115 °C, 20 min).